Radiation synthesis and characterization of poly(ethylene oxide)/chitosan hydrogels. Issue 1 (4th May 2012) - Branca, C.; Auditore, L.; Loria, D.; Trimarchi, M.; Wanderlingh, U.
Abstract Recent advances in hydrogel technology have focused on finding more biocompatible, nontoxic materials intended for pharmaceutical and biomedical applications. In this study, a series of pH‐sensitive hydrogels were prepared from poly(ethylene oxide) (PEO) and chitosan in aqueous solutions by electron beam irradiation. This method is a suitable tool for the formation of biocompatible hydrogels because in radiation processing no initiators or crosslinkers, potentially toxic and difficult to remove, are needed. In this frame, also the PEO and chitosan choice was based on their characteristic of low toxicity. The properties of the prepared hydrogels were investigated in terms of the gel fraction and of the swelling behavior in solutions at different pHs. Some swelling kinetic and diffusional parameters were also determined. The observed properties show that increasing the chitosan content, or lowering the pH, the crosslinking density of these networks increases inducing the formation of more stable, but less swellable, hydrogels. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2012